Dependability, Access Diversity, Low Cost: Pick Two - Chen, Ming; Stein, Lex; Zhang, Zheng (USENIX, 2007)
Storage systems and data centers are growing rapidly and costing more, with higher energy bills. Users want dependable access to a wide variety of diverse content, but providers want to lower costs. Many studies have looked at the tradeoffs between cost and dependability, but few have looked carefully at how content request diversity changes this relationship. In this paper, we model a disk array and develop an analytical framework to study the relationships between dependability, access diversity, and low cost. We show how access diversity changes the relationship between cost and dependability and that all three are in tension with one another. It is possible to improve any two together, but not all three simultaneously.